Predictors of Partial Immunization Among Children Aged 12–23 Months in Yirga Cheffe District, South Ethiopia – A Community-Based Unmatched Case-Control Study - Nenko G; Addisu Y; Eifa A; Ketema W (Dove Medical Press, 2021)
Getachew Nenko,1 Yohannes Addisu,1 Aberash Eifa,2 Worku Ketema3 1School of Public Health, College of Health Sciences, Dilla University, Dilla, Gedio, Ethiopia; 2Department of Midwifery, College of Health Sciences, Hawassa University, Hawassa, Sidama, Ethiopia; 3Department of Pediatrics and Child Health, College of Health Sciences, Hawassa University, Hawassa, Sidama, EthiopiaCorrespondence: Worku KetemaDepartment of Pediatrics and Child Health, College of Health Sciences, Hawassa University, Hawassa, Sidama, EthiopiaTel +251 933207095Email workuketema@gmail.comBackground: Universal age-specific immunization is one of the areas where preventive public health policy has become successful. Despite the increase in global immunization coverage, however, many children around the world, especially in developing countries, are still left unvaccinated. The study aimed at assessing the determinants of partial immunization among children 12- 23 months of age in Yirga Cheffe, Gedeo, Ethiopia.Methodology: A community-based unmatched case-control study design was conducted. Using a simple random sampling technique, 328 samples (164 cases and 164 controls) were selected. Index case was defined as a child aged 12 to 23 months who missed at least one dose of vaccine from the scheduled dose. The odds ratio (OR) and 95% confidence interval (CI) were used to calculate the association, and the level of significance was set at p 0.05.The Result: The study showed that 40% of children were fully vaccinated, and the prevalence of those with partial vaccination was 46%. The likelihood of having incomplete vaccination was 45% higher in children whose mothers had no antenatal coverage (ANC) visit during pregnancy [OR=0.55, (95% CI; 0.297, 1.035)]. Lack of knowledge about the schedule of the vaccination has negatively affected the success of full vaccination (OR=2.3; 95% CI=1.01, 5.56).Conclusion: The study revealed that significant numbers of children are not fully vaccinated. Despite appreciable efforts by the Federal Ministry of Health to improve complete immunization coverage, there are still bottlenecks that need to be tackled in enhancing coverage. We recommend the expansion of ANC and providing education on vaccination schedule and importance to minimize the burden of partial vaccinations and its sequelae.Keywords: partial immunization, 12- 23 month children, Yirgacheffe